IDENTIFIKASI POTENSI WISATA BERDASARKAN KONSEP OPEN-SITE MUSEUM : STUDI KASUS SITUS KERTO PLERET - Sulistyo, Mohammad Yudi; Savitri, Mimi (Jambura History and Culture Journal, 2023)
Reduced visitor interest in the Kerto Site is a major challenge in cultural heritage preservation efforts. To answer these problems, an innovation is needed to increase attractiveness, especially tourist attractiveness. The innovation offered in this research is the Open-site Museum concept. This concept was chosen because of the suitability of the conditions of the Kerto Site and the unfamiliarity of this concept in the ears of the public. This qualitative research is located at the Kerto Pleret Site located in Pleret Village, Bantul Regency, Yogyakarta. The stages of this research are data collection, data processing, and conclusions. The result of this research is to show the tourism potential of the Open-site Museum concept as a unique potential and needs to be educated to the public.